Ecologia vegetal, diversidade entomológica e emissão de Co2 edáfico associado ao uso e manejo do solo - Vital, Maria Janaina Lira (2023)
The maintenance of biodiversity, vegetation cover and greater dynamics of organic matter decomposition significantly contribute to the mitigation of greenhouse gases. The present study aimed to evaluate soil respiration, phytomass decomposition and biodiversity associated with different soil use and management systems. The study was conducted in five systems, namely: Forest, Agroforestry System, Mandala, Mango Orchard and Area invaded by Sporobolus indicus (L.) R. Br. Edaphic respiration was evaluated using containers containing 10 ml of potassium hydroxide and arranged in each system. The infrared gas analyzer (EGM-4) was also used. The analyzes were carried out for 12 hours during the day (5:00 am to 5:00 pm) and 12 hours during the night (5:00 pm to 5:00 am). The evaluation of leaf decomposition was carried out with the species Mimosa caesalpiniifolia Benth. The fresh matter removed from the environment was dried in a forced air circulation oven at 65ºC for 72 hours and placed in litterbags. It was observed that among the areas of the study, the ones that stood out with the highest releases of CO2 at night were the SAF and the Forest and during the day the invaded area. Regarding CO2 analysis methods, it was observed that the values measured with the infrared gas analyzer were much higher than those measured with the alkali absorption method in all systems and months studied. The Forest was the area with the highest rate of decomposition after the SAF. Mandala, Orchard and Invaded Area presented very low values. Phytosociology was analyzed as follows: for soil use and management systems: Forest, SAF and Orchard, five plots were used each, determined by the quadrant method. In the Mandala and Invaded Area systems, the standard inventory square method was used. Entomological diversity was estimated using pitfall traps. 10 traps were distributed in each system and buried randomly in the soil and collected after a period of 48 hours. It was found that the Hymenoptera group was the most frequent in the areas analyzed, in addition, it was seen that the lowest species richness was observed in the Orchard and Mandala areas and the greatest richness was found in the Forest. The environmental variables existing in the type of system, such as temperature, soil humidity and rainfall in the marsh region, influence CO2 effluxes. It is concluded that edaphic respiration together with leaf decomposition analyzes are influenced by the type of management used, as well as biodiversity becomes lower in poorly managed environments.